The value relevance of comprehensive income in Nigerian: A pilot test - Usman, Aliyu Baba; Amran, Noor Afza; Shaari, Hasnah (EconJournals, 2016)
This study is motivated by the need to provide contextual evidence to a decade-long debate regarding accounting standard that require firms to measure certain financial assets and liabilities at fair value and to recognize the effect thereof in a statement of comprehensive income (CI) Nigerian public interest listed firms switch-over to the International Financial Reporting Standards in 2012.Upon this transition, entities are required to report a new summary financial performance indicator known as the CI. This paper investigates the relative value relevance of traditional net income (NI) and the total CI (TCI). We analyzed a sample of 189 firms-year observations comprising of 84 companies listed on the Nigeria Stock Exchange for the period of 2010-2014.While we observed a price and return reactions to the magnitude of both the traditional NI and TCI, our test reveals the supremacy of NI over TCI. By implication, each summary measure is value relevant on an individual basis hence we conclude that both measures reflect information used by investors.